Synthesis, characterization and Molecular docking simulation of novel Atorvastatin Aspirin ester, and study activation effect on lactate dehydrogenase enzyme in atherosclerosis patient - Ghazi Shukr Al-ajeely, Asmaa; Dawood Khalid, Fadhil; Taher Maher, Firas (Tikrit Journal of Pure Science, 2025)
This study involved synthesis of Atorvastatin Aspirin ester prodrug by reacting of aspirin drug with thionyl chloride SOCl2 to produce aspirinyl chloride that mixed with Atorvastatin drug which dissolved with acetone to produce corresponding ester. The structure of new compound was estabilished by spectral techniques that includes FT-IR and 1H-NMR. The biochemical part encompassed collecting of blood samples from atherosclerosis patients then many diluted concentrations of new prepared prodrug and study its effect on the lactate dehydrogenase activity where the outcomes indicated the new ester have activation effect on lactate dehydrogenase enzyme. Molecular docking study was a theoretical investigation to study the interaction of new synthesized ester with Lactate dehydrogenase enzyme (PDB:ID=4i8x), the molecular docking study clarified the synthesized compound showed good docking score: -8.9 kcal\mol with RMSD value 2.819, 5.803 Ao, and binding patterns